How to Promote Diversity and Inclusion in Educational Settings: Behavior Change, Climate Surveys, and Effective Pro-Diversity Initiatives - Moreu, Gil; Isenberg, Naomi; Brauer, Markus (Frontiers in Education, 2021)
We review recent developments in the literature on diversity and inclusion in higher education settings. Diversity interventions increasingly focus on changing behaviors rather than mental constructs such as bias or attitudes. Additionally, there is now a greater emphasis on the evaluation of initiatives aimed at creating an inclusive climate. When trying to design an intervention to change behavior, it is advised to focus on a segment of the population (the “target audience”), to try to get people to adopt a small number of specific new behaviors (the “target behaviors”), and to address in the intervention the factors that affect the likelihood that members of the target audience will engage in the new target behaviors (the “barriers and benefits”). We report our recent work developing a climate survey that allows researchers and practitioners to identify these elements in a particular department or college. We then describe recent inclusion initiatives that have been shown to be effective in rigorous empirical studies. Taken together this paper shows that by implementing techniques based on research in the behavioral sciences it is possible to increase the sense of belonging, success, and graduation rate of students from marginalized backgrounds in STEM.